Cytogenetics analyses among populations of the fish Iheringichtys labrosus (Kröyer, 1874) (Siluriformes, Pimelodidae). Karyotype analysis, C- banding and AgRONs distribution - Sánchez, Sebastián (2014)
Karyotypic data on Iheringichthys labrosus from several populations of Paraná River/Argentina are presented. The diploid number was 2n=56 and the karyotype consisted of 42m/sm + 14st/a (NF= 98). The AgNORs were observed in telomeres of the long arm of a st/a chromosome pair. These sites were also positive after C-banding. Heterochromatin was observed in the telomeric position in some chromosomal pairs and can be found in one or both metacentric chromosome arms. The obtained results were compared with those reported for different populations from Brazilian rivers and the similarity among them was evident. However, discordant chromosome formulae and karyotype features between samples should be carefully taken because, in some cases, they seem to be more technical artifacts than real differences.